2011
DOI: 10.1007/s11252-011-0167-6
|View full text |Cite
|
Sign up to set email alerts
|

Are the closed landfills recovered habitats for small rodents? A case study in a riparian site, Buenos Aires, Argentina

Abstract: The establishment of landfills in urban areas leads to extensive disturbances. Their development after landfill closure depends on the characteristics of the soil cover, the surrounding communities and the dispersal of plants and animals. This study was carried out in a landfill closed in 2004, surrounded by an urban area, freshwater marshes and a riparian forest. The aim of this study was to determine the role that the closed landfill may play in maintaining rodent communities typical of this zone and its rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…O. flavescens was found to be ubiquitous throughout the study area, with highest abundances in the Rolling and Inland Pampas as described elsewhere (Fernández et al, 2012). As observed in our study, other studies conducted in several sites in the Pampas ecoregion have also found that O. flavescens is seldom numerically dominating a small mammal community (Carballido et al, 2011; Maroli et al, 2018; Mills et al, 1991). In contrast, O. flavescens is generally more abundant and often numerically dominant in the Delta ecoregion (Maroli et al, 2021; Massa et al, 2013; Vadell & Gómez Villafañe, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…O. flavescens was found to be ubiquitous throughout the study area, with highest abundances in the Rolling and Inland Pampas as described elsewhere (Fernández et al, 2012). As observed in our study, other studies conducted in several sites in the Pampas ecoregion have also found that O. flavescens is seldom numerically dominating a small mammal community (Carballido et al, 2011; Maroli et al, 2018; Mills et al, 1991). In contrast, O. flavescens is generally more abundant and often numerically dominant in the Delta ecoregion (Maroli et al, 2021; Massa et al, 2013; Vadell & Gómez Villafañe, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…This rodent species acts as reservoir for three genotypes of Andes orthohantavirus (ANDV), the main causative agent of HPS in Argentina (Alonso et al, ; López, Padula, Rossi, Lazaro, & Frenze‐Fernández, ; Martinez et al, ; Rivera et al, ). Population dynamics of O. flavescens was studied in natural (Gómez Villafañe, Expósito, San Martín, Picca, & Busch, ; Vadell, Bellomo, San Martín, Padula, & Gómez Villafañe, ; Vadell & Gómez Villafañe, ), agricultural (Busch & Kravetz, ; Mills, Ellis, McKee, Maiztegui, & Childs, ; Miño et al, ) and urban ecosystems (Carballido, Arístide, Busch, Cittadino, & Gómez Villafañe, ; Cavia, Cueto, & Suárez, ; Muschetto, Cueto, Cavia, Padula, & Suárez, ) of the Central region of Argentina. However, movement ecology of O. flavescens is poorly studied and its home range is still unreported.…”
Section: Introductionmentioning
confidence: 99%
“…Less direct disturbance may contribute to higher species numbers (Dana, 2002;Schadek et al, 2008) by preserving vegetation communities valuable for conservation (Lenzin et al, 2007). Different aspects of vegetation were regarded as important, especially vegetation structure (Fernandez-Juricic, 2000;Florencia Carballido et al, 2011;Geibert, 1980;Strauss and Biedermann, 2006), vegetation as a food source (Eremeeva and Sushchev, 2005;Kazemi et al, 2011;Tommasi et al, 2004), and vegetation (including tree) cover (Ichinose, 2006;Itagawa et al, 2010;Luther et al, 2008;Pennington et al, 2008). Biodiversity was found to increase with site age (Crowe, 1979;Jantunen et al, 2006;Kim and Lee, 2005), distance from the city center (Vakhlamova et al, 2014;Wahlbrink and Zucchi, 1994;Zorenko, 2003), and habitat diversity (Dallimer et al, 2012b;Murgui, 2009), while it was negatively affected by sealed site surface (e.g., hard surfaces such as asphalt that can impede seedling growth) and substrate (Dallimer et al, 2012b;Francis and Hoggart, 2008;Godefroid et al, 2007).…”
Section: 1(b) Factors Influencing Igs Biodiversitymentioning
confidence: 99%